Phylogenetic Affiliation of the “Endong” “Spaghetti” Variety of Eucheuma as Revealed by Molecular Data - Montes, Humberto Jr (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2008)
A carrageenan-producing seaweed locally referred to as “Endong”/ “Spaghetti” and initially regarded by farmers as a variety of Kappaphycus on the basis of morphological similarity has recently been shown to be a variety of Eucheuma, as indicated by its histological features and carrageenan type. Considering its unique combination of characteristics, it is of interest to determine the phylogenetic relationship of this seaweed with Kappaphycus and Eucheuma varieties. Three genetic markers were sequenced and analyzed to ascertain its phylogenetic affiliation: RuBisCo (rbc) spacer, a portion of the cytochrome oxidase subunit I (cox1) and a small segment of the plastid genome (URP1). Two samples separately collected from two sites (referred to by farmers as “Endong” and “Spaghetti”) were used. Phylogenetic analysis of the rbc spacer sequences confirmed the affiliation of “Endong”/ “Spaghetti” with Eucheuma; their rbc spacer sequences are in fact highly similar to that of E. denticulatum. Results of the analysis of cox1 and URP1 sequences, which were found to be slightly more polymorphic than the rbc spacer, were consistent with the results of the rbc spacer sequence analysis.